Klausula Baku Dalam Perspektif Asas Kebebasan Berkontrak Ditinjau Dari Undang-Undang Perlindungan Konsumen - Helena Primadianti Sulistyaningrum; Dian Afrilia (Simbur Cahaya, 2020)
The existence of standard clause is commonly seen in the world of commerce or business today. The sandard clause is clearly made unilaterally by the business actors. Consumers as a user of products or services pay less attention to this, unless a certain loss happened. Actually, in the standard clause should applied the principle of freedom of contract which is ruled in a contract. That principle is being fundamental for the existence of standard contract in regulating the legal relationship between business actors and consumers, but the implementation of this principle requires that the parties on their contract have a balanced position. So, how is the standard clause in the perspective the principle of freedom of contract according to the Consumers Protection Act. Therefore, a limitation is needed in the using of the standard clause in order to palce the same position between business actor and consumers based on the principle of freedom of contract